Overview of the Level of Public Knowledge about Diabetes Mellitus, Tuberculosis and Stunting in Tosa Village - Tutik Lestari; Retno Kartika Aldjokdja; Sabaria Sumarto; Ruslia Daud; Siti Aigina Langasa; Tiara Manteto; Wahdi Bada (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Knowledge of health issues is crucial for maintaining and improving quality of life. This includes understanding the disease, its causes, symptoms, prevention, and treatment. Diabetes mellitus, tuberculosis, and stunting are interrelated health issues that can worsen a person's health condition. This study aims to determine the public's knowledge of diabetes mellitus, tuberculosis, and stunting in Tosa Village. This study is a descriptive analytical epidemiological study. The research design used a survey method. The population was the entire census block of 153 people with a sample of 142 people. The results showed that respondents' knowledge of diabetes mellitus was in the low category, at 62%. Meanwhile, knowledge of tuberculosis was included in the high category at 55.6%, and knowledge of stunting was also high at 58.5%. Based on the results of this study, the level of respondents' knowledge varied regarding each disease, therefore, health education related to these three health issues (diabetes mellitus, tuberculosis, and stunting) is necessary.